Vasculitis induced by biological agents used in rheumatology practice: A systematic review - Camila da Silva Cendon Duran; Adriane Souza da Paz; Mittermayer Barreto Santiago (Archives of Rheumatology, 2022)
Objectives: Biological medications have been used with an increasing frequency to treat rheumatological diseases. Autoimmune events can be induced by these drugs, such as psoriasiform lesions, alopecia, lupus and, vasculitis, which more often affects the skin (small-sized vessels) and eventually other organs. In this review, we describe the clinical profile of patients with vasculitis induced by the main biological agents used in rheumatology. Patients and methods: We performed a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. The PubMed database was used for searching eligible articles. We included case reports, case series, and letter to the editor of patients on anti-tumor necrosis factor-alpha (anti-TNF-a) molecules, as well as tocilizumab, ustekinumab, secukinumab, rituximab, and abatacept, who had vasculitis induced by these agents. Results: Eighty-one articles were included for final analysis (n=89). Twenty-seven patients were using infliximab, 20 adalimumab, 18 etanercept, seven secukinumab, four certolizumab, four rituximab, three golimumab, three ustekinumab, two abatacept, and one tocilizumab. Unspecific leukocytoclastic vasculitis (LCV) was the most common type of vasculitis (n=37), followed by anti-neutrophil cytoplasmic antibody (ANCA)- associated vasculitis (n=16). The medication was replaced with another biological molecule in 23 cases, with only four relapses. In six cases, the biological was maintained, but vasculitis worsened/persisted in one case, being necessary drug removal. Conclusion: Infections, infusion reaction, cancer, and autoimmune events are well-known side effects of biological therapy. This review demonstrates that vasculitis is another adverse effect of this type of therapy, particularly the anti-TNF-a molecules, and LCV the most reported type of vasculitis.